PENGOBATAN MENGGUNAKAN KAYU INDIA (GAHARU) DALAM PERSPEKTIF HADIS DAN SAINS - Abdul Halim; Muhammad Nuh Siregar; Misna Hasibuan (SHAHIH (Jurnal Ilmu Kewahyuan), 2021)
Gaharu wood is wood that grows in Southeast Asia and South Asia, Gaharu itself is produced by resin, made from microbes that enter into tree wounds or cuts on tree trunks and have many benefits. In line with the main research, this study aims to determine the quality of the Hadith in the Hadith which discusses the treatment using agarwood which is analyzed through the Hadith narrated by Imam Ahmad bin Hanbal. Agarwood in pharmacology is very influential and important as an ingredient for making medicines. As explained by the Prophet Muhammad. in the Hadith that agarwood can cure various diseases and become a very special wood in the history of the Prophet.